Adoption; a relevant concept for agricultural land management in the 21 century?. (December 2022) - Allan, Catherine; Cooke, Penelope; Higgins, Vaughan; Leith, Peat; Bryant, Melanie; Cockfield, Geoff
This review seeks to understand the implications of using "adoption" to evaluate agricultural soil management outreach in the twenty-first century. The act of changing from one practice to another practice is referred to as "adoption". The concept of adoption is closely associated with the design and evaluation of agricultural extension programs. Although focusing on adoption is deeply entrenched in agricultural extension, some scholars question the usefulness of the concept in light of the complexity and uncertainty that characterises farming in the twenty-first century. We present a purposeful review of literature that considers adoption in relation to three general approaches to agricultural extension; top-down, bottom-up and co-constructionist, with an emphasis on land management in Australia. The conceptual fit of adoption as a measure of success for each extension approach is explored. We conclude that the usefulness of adoption of individual practices or tools as a measure of success needs to be considered in context. Failing to reflect on what adoption means in any particular program or activity risks ignoring or misunderstanding real change and impacts and /or shaping activities to fit a simple, linear adoption expectation. We suggest that adoption remains a useful concept, but could be best considered as a gateway to increased reflection and reflexivity when projects and activities are being developed.